Efektivitas Penggunaan Buku Durusul Lughah al-Arabiyyah untuk Meningkatkan Mahārah al-Kitābah di Kulliyatul Mu’allimīn Wal Mu’allimāt al-Islāmiyyah al-Barokah Nganjuk - Nur Habib Ahmad Hambali; Rina Dian Rahmawati; Aufia Aisa (Lembaga Yasin AlSys, 2026)
Mastery of mahārah al-kitābah is one of the fundamental competencies in Arabic language learning that reflects not only mastery of grammar and vocabulary but also the ability to think critically and systematically. This study aims to examine the effectiveness of using the book Durusul Lughah Al-Arabiyyah in improving the writing skills of fifth-grade students at Kulliyatul Mu’allimin Al-Islamiyah (KMI), which is equivalent to Grade XI of senior high school. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The research participants consisted of 40 students divided into an experimental class and a control class, with 20 students in each class. The experimental class received instruction using the book Durusul Lughah Al-Arabiyyah, whereas the control class used the conventional book Tamrin Al-Lughah. Data were collected through written essay tests in the form of pretests and posttests, observation, and documentation. The results showed that the experimental class achieved a mean posttest score of 72.00 (SD = 14.09), which was higher than the control class’s mean score of 52.50 (SD = 10.07). The research instrument demonstrated high reliability, with a Cronbach’s alpha value of 0.862. The independent-samples t-test yielded a calculated t-value of 5.03 with p < 0.05, indicating a significant difference between the two groups. Thus, the use of the book Durusul Lughah Al-Arabiyyah was effective in improving students’ mahārah al-kitābah. These findings provide practical implications for educators in selecting systematic instructional materials to improve the quality of Arabic writing skills instruction.